Dual-species biofilms of Streptococcus mutans and Candida albicans exhibit more biomass and are mutually beneficial compared with single-species biofilms - Lobo, Carmélia Isabel Vitorino [UNESP]; Rinaldi, Talita Baptista [UNESP]; Christiano, Chiara Mikaella Somogyi [UNESP]; De Sales Leite, Luana [UNESP]; Barbugli, Paula Aboud [UNESP]; Klein, Marlise Inêz [UNESP] (Taylor & Francis, 2019)
Background: Streptococcus mutans (Sm) and Candida albicans (Ca) are found in biofilms of early childhood caries. Objective: To characterize in vitro dual- and single-species biofilms of Sm and Ca formed on saliva-coated hydroxyapatite discs in the presence of sucrose. Design: Evaluation of biofilms included biochemical [biomass, proteins, matrix’s water-soluble (WSP) and alkali-soluble (ASP) polysaccharides, microbiological, 3D structure, gene expression, and stress tolerance analyses. Results: Biomass and proteins were higher for dual-species and lower for Ca (p = 0.001). Comparison of Sm single- and dual-species biofilms revealed no significant difference in Sm numbers or quantity of WSP (p > 0.05). Dual-species biofilms contained a higher population of Ca (p < 0.001). The quantity of ASP was higher in dual-species biofilms (vs Ca single-species biofilms; p = 0.002). The 3D structure showed larger microcolonies and distinct distribution of Sm-derived exopolysaccharides in dual-species biofilms. Compared with dual-species biofilms, expression of gtfB (ASP) and nox1 (oxidative stress) was higher for single-species of Sm whilst expression of BGL2 (matrix), PHR1 (matrix, acid tolerance) and SOD1 (oxidative stress) was higher in single-species of Ca. There was no difference for acid tolerance genes (Sm atpD and Ca PHR2), which was confirmed by acid tolerance challenge. Dual-species biofilms were more tolerant to oxidative and antimicrobial stresses (p < 0.05). Conclusions: Dual-species biofilms present greater 3D complexity, thereby, making them more resistant to stress conditions.
Keywords: 3D architecture; Biofilm; Candida albicans; gene expression; Streptococcus mutans; stress tolerance